Stress and coping of English learners in the 21st century - Rishel, Teresa; Miller, Paul Chamness (Research in stress and coping in education, 2018)
Stress and Coping of English Learners addresses the many ways that ELs face academic and socioemotional stress in the K-12 school environment, the consequences of this stress at school, how they cope with this stress, and how school personnel and families can provide support and help. While enrollment in school programs offers assistance to many ELs, it often fails to provide the socioemotional support that ELs need as they navigate the rough waters of schooling. American schooling is often not prepared and/or unwilling to help ELs as they adapt to an unfamiliar language, culture, social norms, communication techniques, and teachers' expectations. Given the proper foundation and emotional support, ELs will be positioned for greater academic success, comfort at school, and a decrease in their sense of alienation in both the school environment and at home as they try to negotiate between two cultural environments.